1999
DOI: 10.1101/gad.13.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Binding of hnRNP H to an exonic splicing silencer is involved in the regulation of alternative splicing of the rat beta -tropomyosin gene

Abstract: In the rat ␤-tropomyosin (␤-TM) gene, exons 6 and 7 are spliced alternatively in a mutually exclusive manner. Exon 6 is included in mRNA encoding nonmuscle TM-1, whereas exon 7 is used in mRNA encoding skeletal muscle ␤-TM. Previously, we demonstrated that a six nucleotide mutation at the 5 end of exon 7, designated as ex-1, activated exon 7 splicing in nonmuscle cells. In this study, we show that the activating effect of this mutation is not the result of creating an exonic splicing enhancer (ESE) or disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(159 citation statements)
references
References 64 publications
12
147
0
Order By: Relevance
“…6B). The effect observed with hnRNP A1 was surprising, because hnRNPs were shown primarily to mediate splicing repression from exonic positions (60)(61)(62). Nevertheless, a study performed in parallel with our work recently reported the same effect of hnRNP A1 on FAS exon 6 splicing (63).…”
Section: Discussionsupporting
confidence: 64%
“…6B). The effect observed with hnRNP A1 was surprising, because hnRNPs were shown primarily to mediate splicing repression from exonic positions (60)(61)(62). Nevertheless, a study performed in parallel with our work recently reported the same effect of hnRNP A1 on FAS exon 6 splicing (63).…”
Section: Discussionsupporting
confidence: 64%
“…hnRNP H1 belongs to the superfamily of heterogeneous nuclear ribonucleoproteins (hnRNPs). It binds to intronic oligo-(G) sequences and regulates alternative exons negatively or positively, depending upon the context (Chen et al 1999;Chou et al 1999;Jacquenet et al 2001;Caputi and Zahler 2002;Garneau et al 2005;Crawford and Patton 2006). It was recently shown that hnRNP F and hnRNP H form a complex with RBFOX2, and this interaction enhances hnRNP H/F's ability to antagonize SRSF1 binding to FGFR2 exon IIIc (Mauger et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As a second approach to identifying proteins that interact with SEa2, northwestern blotting was performed+ The radiolabeled SE80 probe bound primarily to the 34-kDa band in the SR protein fraction (Fig+ 6A, , and SC35 (lane 5, 0+1 mg) were analyzed by SDS-PAGE, blotted, and probed with 32 P-labeled SE80 RNA+ Lower panel: Parallel western blot analysis of gel run with the same samples+ The blot was developed with SF2/ASF-specific antibody+ The migration of endogenous, phosphorylated SF2/ASF (hSF2) from HeLa cells and recombinant, nonphosphorylated SF2/ASF are indicated at the right on both panels+ B: Immunoprecipitation of crosslinked proteins with SF2/ASF-specific antibody+ SE80 was incubated in nuclear extract under splicing conditions for 30 min and then UV crosslinked+ Input lane (lane 1) represents 8% of the UV-crosslinked splicing reaction, which was subsequently immunoprecipitated with an SF2/ASF-specific antibody (lane 2) or a control antibody (lane 3)+ Proteins were resolved by SDS-PAGE on a 12% gel+ C: Immunoprecipitation of labeled SE80 with hnRNP H-and F-specific antibodies+ Input lanes at two exposures (lanes 1 and 2) are 4% of the reaction that was used in the immunoprecipitations using polyclonal antibodies specific for hnRNP H (lane 3), or hnRNP F (lane 4), or preimmune serum (lane 5)+ the 55-kDA crosslinked protein+ As shown in Figure 6B, SF2/ASF, labeled by UV crosslinking to SE80, was specifically precipitated with a monoclonal antibody specific for SF2/ASF (lane 2), but not by antibodies prepared in a similar fashion to a control antigen (lane 3)+ A similar approach was used to identify the abundant 55-kDa protein+ Because this protein is present in the S100 extract but not the SR protein preparation, possible candidates include hnRNP F or hnRNP H, two closely related RNA-binding proteins that are known to bind to splicing regulatory elements (Chen et al+, 1999;Chou et al+, 1999;Fogel & McNally, 2000)+ As shown in Figure 6C, a polyclonal antibody specific for hnRNP H (Chou et al+, 1999) efficiently precipitated a 55-kDa crosslinked protein comigrating with the most intense input band, thereby confirming that hnRNP H was crosslinked to SE80 (Fig+ 6B, lane 3)+ A polyclonal antibody that specifically recognizes hnRNP F precipitated a small amount of crosslinked hnRNP F that migrates immediately below hnRNP H (Fig+ 6B, lane 4)+ On the basis of these results, we conclude that SF2/ASF and hnRNP H are two of the major proteins that bind to SEa2+…”
Section: Sf2/asf and Hnrnp H Bind Specifically To Sea2mentioning
confidence: 99%
“…Like the 55-kDa crosslinked protein, both hnRNP F and hnRNP H proteins are present in S100 and nuclear extract but not in the SR protein preparation, migrate between 50 and 60 kDa, and bind G-rich intronic splicing enhancer elements (Matunis et al+, 1994;Chou et al+, 1999)+ We confirmed this interaction by antibody-specific immunoprecipitation of hnRNP H and F crosslinked to SE80+ The intense 55-kDa band corresponds to hnRNP H whereas hnRNP F comigrates with a much fainter band just in front of hnRNP H (Figs+ 6C and 9B)+ Although this result may simply reflect differences in the efficiency of crosslinking and immunoprecipitation, it is likely that hnRNP H is the major protein species bound to SEa2 and that hnRNP F binds to only a relatively small fraction of SEa2 transcripts+ SE60, which displays a high level of splicing enhancer activity (Fig+ 7B), also binds hnRNP H and F (Fig+ 9B), whereas SE60Ϫ1CCA, SE50, and SE40, which lack significant splicing enhancer activity, do not bind efficiently to hnRNP H+ Thus, interactions of SEa2 with hnRNP H and F correlate with splicing enhancer activity, suggesting that these proteins are involved in SEa2 function+ hnRNP H and hnRNP F have been shown to activate neural-specific splicing of c-src mRNA (Min et al+, 1995;Chou et al+, 1999)+ This enhancer sequence is located in the intron downstream of the regulated exon+ The Rous sarcoma virus (RSV) primary RNA transcript also contains an intronic element, NRS, that interacts with hnRNP H to regulate splicing (Fogel & McNally, 2000)+ However, in this case, hnRNP H mediates NRSdependent splicing inhibition+ hnRNP H is also implicated in the inhibition of rat b-tropomyosin splicing (Chen et al+, 1999)+ As observed with the c-src enhancer, hnRNP H bound to SEa2 may promote TRa2 splicing+ Inhibition or enhancement of splicing by hnRNP H does not appear to be determined by the location of the regulatory sequences but is likely to be influenced by specific interactions with other factors+ A pseudo-59 splice site sequence is critical for SEa2 activity Deletion analysis of SEa2 showed that the 9-nt region present in SE60 but not SE50 overlaps a 59-splice-sitelike sequence that is essential for SEa2 activity (Fig+ 7)+ Interestingly, two single nucleotide substitutions (Ϫ2A or ϩ6U) at relatively peripheral sites, as well as other substitutions that increase the match to the consensus 59 splice site (SE60Ϫ4AAA, SE60ϩ2AA), activate efficient cryptic splicing at this site+ This cryptic splicing does not occur in wild-type pre-mRNAs and thus the sequence represents a pseudo-59 splice site+…”
Section: Hnrnp H and Hnrnp F Interact With Sea2mentioning
confidence: 99%